Żniwa – święty czas pracy. Malarstwo i pamięć dzieciństwa - Kępiński, Marcin (Zeszyty Wiejskie, 2016)
The article is an attempt of analysis of Włodzimierz Tetmajer’s chosen works concerning the harvest. I am also describing images of the harvest on the Polish village of Kamionka, being in surroundings of Chełm, which I remembered from the childhood. I am appealing to reality of the myth of the happy village, current in Polish painting and literature. I am taking it back to observed remains of folk customs and the traditions bond with the harvest.